Biomass accumulation of microalgae for biofuel production - Кирилова, А. О.; Матюхін, І. В.; Карпенко, В. І. (Problems of Environmental Biotechnology, 2015)
Techniques of microalgae isolation from natural water sources and methods of green algae associations cultivation were tested. Pure cultures of green algae Chlorella vulgaris and Monoraphidium tortile were isolated by cultural and morphological characteristics using spread plate and streak plate techniques. Batch culture of isolated algae was performed. It was established that Chlorella vulgaris specific growth rate – 0,28×106 cells/ml∙day, 43,8×106 cells/ml∙day performance, and lipid composition equal to 14–22 %, respectively, and for Monoraphidium tortile specific growth rate – 0,30×106 cells/ml∙day, productivity – 65,1×106 cells/ml∙day, lipid composition equal to 56,8 %. By comparing these characteristics it was found that research culture fit all criteria for the selection of algae for biofuel production.